TNFAIP3 Gene Polymorphisms in a Chinese Han Population with Vogt–Koyanagi–Harada Syndrome - Li, Hong (Public Library of Science, 2013)
BACKGROUND: This study was performed to evaluate the potential association of TNFAIP3 polymorphisms with Vogt–Koyanagi–Harada (VKH) disease in a Chinese Han population. METHODOLOGY/PRINCIPAL FINDINGS: Five single-nucleotide polymorphisms (SNPs), rs10499194, rs610604, rs7753873, rs5029928 and rs9494885 of TNFAIP3 were genotyped in 834 VKH disease patients and 1415 healthy controls using a PCR-restriction fragment length polymorphism assay. An increased frequency of the C allele and CT genotype for rs9494885 were found in VKH patients in the Guangzhou and Chongqing cohorts (pc = 0.015, OR = 1.6, pc = 0.036, OR = 1.7; pc = 2.36×10−4, OR = 1.5, pc = 0.012, OR = 1.5, respectively). Meanwhile, a decreased frequency of the TT genotype for rs9494885 was observed in VKH patients in the Guangzhou and Chongqing cohorts (pc = 0.026, OR = 0.6, pc = 0.0074, OR = 0.7, respectively). The combined analysis showed that a significantly increased prevalence of the rs9494885 TC genotype and C allele were found in VKH disease patients compared with controls (pc = 2.26×10−5, OR = 1.7; pc = 1.09× 10−5, OR = 1.6, respectively). The frequency of the TT genotype of rs9494885 was markedly lower in VKH disease patients as compared with that in controls (pc = 1.12×10−5, OR = 0.6; p(c) = 1.09×10(−5), OR = 0.6, respectively). No association was found between rs10499194, rs610604, rs7753873 and rs5029928 polymorphisms and VKH disease. To our knowledge this is the first report describing the association of a TNFAIP3 gene polymorphism with VKH disease in a Chinese Han population. CONCLUSIONS/SIGNIFICANCE: The results suggest that the rs9494885 TC genotype and C allele may be predisposing factors to VKH disease, whereas the rs9494885 TT genotype and T allele may provide protection against this disease.